FACTORES QUE INHIBEN A LOS PADRES DE FAMILIA EN EL APOYO FORMATIVO - ACADÉMICO DE LOS ESTUDIANTES DE LA ESCUELA DE EDUCACIÓN BÁSICA TUNGURAHUA Nº 12 DE LA PARROQUIA SAN CARLOS, CANTÓN QUEVEDO, PROVINCIA DE LOS RÍOS. - Monrroy Arellano, Rosario Isabel (2014)
This research identifies factors that inhibit parents training support - academic students of the school tax mixed Tungurahua No. 12 of the parish San Carlos canton Quevedo, Los Ríos province, for its effect was identified the level of participation of parents in the process teaching their children's learning Likewise settled the consequences of the current parent involvement, results that led to the design of strategies and methods to encourage the contribution of parents in the learning process of learners. The Ríos province, conducted the study is in the premises of the school tax mixed Tungurahua Nº 12, located in the San Carlos parish of Quevedo canton, which took into account 228 students, 228 parents and 17 teachers from educational institution, whereas the academic year 2014-2015. To achieve the objectives of the present study went to the implementation of the types, methods, techniques and instruments of research, with the purpose of collecting primary information about the object of study, similarly used documentary bibliographic method to quote several themes focused on the variables of the investigation, which led to the discussion of results and verification of hypotheses. The proposal "Coexistence workshop to promote the participation of parents in the process of teaching-learning of the Fiscal school students mixed Tungurahua Nº 12 parish San Carlos, Quevedo canton, through methodological strategies", was born through a study on the factors that inhibit parents in training - academic of the students of the educational institution - supported study where evidence of factors that disturb the participation of parents in the development of the tasks of their children. Therefore, that is born the idea of action and assumes positive activities to eradicate the problem and to involve parents in the process. He is expected that the proposal will help positively education as a learning process, necessitating rethinking the role that education plays in finding alternatives that will allow guide and make the change in the classroom.